2015
DOI: 10.4236/jct.2015.611108
|View full text |Cite
|
Sign up to set email alerts
|

Local Excision of Early Rectal Cancer by Transanal Endoscopic Microsurgery (TEM): The 23-Year Experience of a Single Centre

Abstract: Aim: Transanal endoscopic microsurgery (TEM) is an effective, minimally invasive alternative approach to traditional surgery. This study reviews the characteristics of a series of patients affected by early rectal cancer and discusses the results of this treatment. Methods: From 1992 to 2014, 187 patients with rectal cancer staged as pT1 by preoperative endorectal ultrasound, computerized tomography and/or magnetic resonance imaging were treated by TEM at our institution. We analysed age, gender, size of lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Any local technique which attains this goal should produce equivalent results. Recent improvements in techniques for transanal excision have consistently shown that in most surgeons' hands traditional transanal excision is inferior to newer techniques [9,10]. For that reason, if transanal tumor excision is planned, an advanced technique with rectal insufflation, magnified vision, and precise surgical instrumentation should be used.…”
mentioning
confidence: 99%
“…Any local technique which attains this goal should produce equivalent results. Recent improvements in techniques for transanal excision have consistently shown that in most surgeons' hands traditional transanal excision is inferior to newer techniques [9,10]. For that reason, if transanal tumor excision is planned, an advanced technique with rectal insufflation, magnified vision, and precise surgical instrumentation should be used.…”
mentioning
confidence: 99%